2015
DOI: 10.1021/acs.jafc.5b03889
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Stabilization of Whey-Based Monodisperse Nanoemulsions Using Ultra-High-Pressure Homogenization and Small Amphipathic Co-emulsifier Combinations

Abstract: Ultra-high-pressure homogenization (UHPH) was used to generate monodisperse stable peanut oil nanoemulsions within a desired nanosize range (<100 nm) (DNR) stabilized using combinations of whey protein concentrate (WPC), sodium dodecyl sulfate, Triton X-100 (X100), and zwitterionic sulfobetaine-based surfactants differing in hydrophobicity. For WPC [2.0% (w/v)], the dispersed-phase fractions (φ) of 0.05 and 210 MPa significantly reduced the mean globule size (dvs) but the grouped frequency distribution was bim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…1. The two treatments both exhibited a unimodal particle size distribution, while the average particle size of SP-PC nanoemulsions prepared by ultrasound treatment was 282.4 nm, which was significantly larger than that of high-pressure homogenization 21 . Seidmahdi et al .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…1. The two treatments both exhibited a unimodal particle size distribution, while the average particle size of SP-PC nanoemulsions prepared by ultrasound treatment was 282.4 nm, which was significantly larger than that of high-pressure homogenization 21 . Seidmahdi et al .…”
Section: Resultsmentioning
confidence: 81%
“…Zhang et al . 21 reported that high-pressure homogenization could break the emulsion droplets into smaller species to stabilize nanoemulsions and α-helix structures of soybean protein isolates by intense turbulence, vibration, cavitation and hydraulic shear. The increased unordered structure induced by high-pressure homogenization was related with the increased flexibility of protein structure, which could determine that the emulsifying properties and structures rearranged rapidly on the interface 38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…proteins and starches, will change due to the strong shearing force, high-speed impact, high-frequency oscillation, instantaneous pressure release, and other dynamic actions applied to the materials in the reaction chamber, resulting in certain changes in the functional properties of the materials [10][11][12] . Dynamic UHPH has been used to improve the functional properties of peanut protein [13] , soy protein [14] , whey protein [15] , and others. However, few studies have been reported on the application of dynamic UHPH to improve the functional properties of casein.…”
Section: Introduction mentioning
confidence: 99%
“…Both Tween-80 and PVA is commonly used as emulsifier in preparation microspheres. The research found that the co-emulsifier can help improving emulsifying performance (Zhang & Haque, 2015). In the present study, Tween-80 and PVA is used as the co-emulsifier to help enhance the quality of microspheres.…”
Section: Surface Morphology Of Microspheresmentioning
confidence: 85%